Voix soufflées, voix volées, voix intervocales - Helga Finter (Sillages Critiques)
This article goes against the grain of the vision of the new American theatre as a “theatre of images” (Bonnie Marranca), to which it substitutes an analysis of the theatricalization of voice. As an acoustic image of the body, voice makes it possible to play on atopia, and the circulation and separation from the sender, creating effects of disjunction whose destabilizing power modifies the conventional conditions of perception and reception. The roles of the director and sound designer are then transformed. The analysis is based on a body of productions from the 1970s onwards, including works by Robert Wilson, Lee Breuer and the Wooster Group, and foregrounds the possibilities offered by technology in the treatment and alterations of voice in the theatre.American Theatre, Laurie Anderson, Robert Ashley, body, Lee Breuer, Meredith Monk, technology, theatricality, voice, Robert Wilson, Wooster Group